Value Addition and Consumers’ Satisfaction Compromise: A Case of Raphia Wine Supply Chain in Imo State, Nigeria - Ehirim, N. C.; Okere, R. A.; Ikheloa, E. (Advances in Social Sciences Research Journal, 2019)
Despite increased patronage, stakeholders’ participation is fingered in inefficiencies along raphia wine supply chain. The extent which consumers’ utility is compromise is beclouded by the margin and no study has established it. Two stage sampling technique was used to draw 32 processor-marketers and 48 wine vendors from the supply markets as well as 91 consumers drawn from the destination market to give 171 sample size. Simple descriptive statistics, marketing margin, budgetary analysis and econometric tools were used in the analyses. Gross margin of <s>N53.03/litre and <s>N36.51/litre for retailers and processor-marketer respectively, representing 39.8% profit differentials and a marketing margin of <s>N60.03/litre were recorded. Although it is profitable, value added of <s>N123.41/litre has N9.92/litre of utility compromised, hence, increased marketing margin is taking advantage of consumers’ preference and utility in the system. Utility compromise is reduced by 5.9% and 4.8% with a unit increase in raphia marketing as a major occupation and cost of marketing services but increased by 4.6%, 19.5%, 2.3% and 33.5% with a unit increase in the number of years in the business, distance from the area of supply, co-operative membership and unique selling device employed by the retailer respectively. Majority (94.51% and 90.0%) complained that unorganized marketing system especially the lack in unique selling device and poor product standardization characterized by an unorganized utility threshold in the system may be the reason but high patronage is envisaged if 21.98% consumers who prefer brewed alternative buy local raphia wine. The study recommends a policy that will tackle an organization and standardized market and products to reduce utility compromise in the supply chain.</s></s></s></s> <s><s><s><s> </s></s></s></s>